Meninjau Kembali Evolusi Pemasaran Asuransi Syariah: Media Sosial sebagai Katalis Inovatif dalam Menarik Klien Milenial - Mutiara Dewi; Khairina Tambunan; Nurwani (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study examines the evolution of digital marketing strategies employed by sharia-compliant insurance providers through social media, with a particular focus on their efficacy in engaging the millennial demographic in Perbaungan City. Adopting a qualitative research design, data were collected via systematic observation of digital content, documentation analysis, and in-depth interviews. Findings indicate that Facebook constitutes the predominant platform through which millennials access information on sharia insurance, accounting for 74.09% of user engagement, followed by TikTok (31.72%) and Instagram (22.14%). The most impactful promotional approaches comprise the deployment of interactive content, strategic collaborations with influencers, and the dissemination of educational yet compelling informational material. Furthermore, millennials display a marked preference for digital endorsements over conventional advertising. In light of these insights, sharia insurance providers are urged to refine and intensify social media–driven marketing strategies to ensure greater relevance, resonance, and alignment with the distinct needs and preferences of the millennial generation